The Interrelationship of Indonesia-China-India in Religion from Arabian Islam to Nusantara Islam - Mudzakkir Ali; Mehmet Toprak (Proceeding Of The International Seminar and Conference on Global Issues, 2015)
Nusantara Islam is an implementing of Islamic teachings in the region of Nusantara (it is called Indonesia now). Nusantara Islam does not appear in sudden, but it has a long historical process as the effect of the acculturation of the relationship of Indonesian with Arab and Persian, who areMuslims, andthe culture of Chinese and Indian,who are Buddhists/Hinduisms, which has become the nation’s characteristics. The traditional knowledgethat is built by the muftis (especially Walisongo), especially through pesantren produces Islam with the support of majority of people, i.e.,the view of Ahlus Sunnah wal Jama’ah (Aswaja). Thus, the core value of Aswaja is to maintain thegood traditional inheritance valueand to take/search forthe better new tradition, which is supported by the moderate, fair, tolerantand proportional attitude in all of life fields.   Keywords: Islam, Arab, Nusantara, Pesantren, Aswaja